2015
DOI: 10.1259/bjr.20140470
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac MR assessment of microvascular obstruction

Abstract: Microvascular obstruction (MVO) is usually seen in a proportion of patients with acute myocardial infarction following reperfusion therapy of an occluded coronary artery. It is characterized by damage and dysfunction of the myocardial microvasculature with a no-reflow phenomenon within the infarct zone. While MVO may be demonstrated via a number of different imaging modalities, cardiac MR (CMR) enables accurate identification of MVO and also permits assessment of infarct extent and overall left ventricular fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 10 publications
0
31
1
4
Order By: Relevance
“…The presence of MVO is increasingly recognized as a poor functional recovery indicator since it represents more severe myocardial as well as microvasculature damage . However, conflicting data exist with respect to the MVO presence and regional function recovery.…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations
“…The presence of MVO is increasingly recognized as a poor functional recovery indicator since it represents more severe myocardial as well as microvasculature damage . However, conflicting data exist with respect to the MVO presence and regional function recovery.…”
Section: Discussioncontrasting
confidence: 61%
“…The presence of MVO is increasingly recognized as a poor functional recovery indicator since it represents more severe myocardial as well as microvasculature damage. 2,15 However, conflicting data exist with respect to the MVO presence and regional function recovery. Some studies 6,[26][27][28] showed no significant functional recovery in segments with MVO, which is contrary to the findings of Nijveldt et al 8 : wall thickening improved equally in segments with and without MVO in nontransmural segments (ie, DHE transmural extent <75%); but less improved in transmural segments (>75%) with MVO than in transmural segments without MVO, suggesting a complex interplay between DHE transmural extent and MVO presence.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Cardiac magnetic resonance imaging (CMR) can quickly assess infarct size and is considered as the gold standard for MVO evaluation and quantification [4,7,8]. By the way, CMR provides ventricular function and volumes [9], but its availability remains a problem, urging for identification of alternative markers of bad outcomes, and several biomarkers have been evaluated to assess MVO [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%